2018
DOI: 10.1002/acr.23594
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Systemic Lupus Erythematosus Show an Increased Arterial Stiffness That is Predicted by IgM Anti–β2‐Glycoprotein I and Small Dense High‐Density Lipoprotein Particles

Abstract: SLE patients show increased arterial stiffness compared to a healthy population. Patients treated with antimalarial drugs show lower arterial stiffness. Age, IgM-ß2-GLP-I and the number of small dense HDL particles predicted the AIx. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Rheological studies demonstrated how SLE patients present higher blood viscosity and RBC deformability, and aggregation rates, correlating with disease severity and cardiovascular complications 95,98,273 . Arterial stiffness in SLE patients was found to be affected, as reported in a number of clinical studies for different drugs and disease severity diagnoses 274–277 …”
Section: Autoimmune Diseasesmentioning
confidence: 75%
See 1 more Smart Citation
“…Rheological studies demonstrated how SLE patients present higher blood viscosity and RBC deformability, and aggregation rates, correlating with disease severity and cardiovascular complications 95,98,273 . Arterial stiffness in SLE patients was found to be affected, as reported in a number of clinical studies for different drugs and disease severity diagnoses 274–277 …”
Section: Autoimmune Diseasesmentioning
confidence: 75%
“…95,98,273 Arterial stiffness in SLE patients was found to be affected, as reported in a number of clinical studies for different drugs and disease severity diagnoses. [274][275][276][277] Inflammatory rheumatic diseases are a group of ADs affecting the motor and joint systems. 278 Rheumatoid arthritis has been associated…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…Among disease-related features, we found an association between cfPWV and anti-β2GPI IgM positivity. Interestingly, Parra et al [ 39 ] have also shown a significant association between AIx levels and positive anti-β2GPI IgM in SLE patients ( p = 0.035). We also demonstrated that cfPWV was independently associated with femoral artery atherosclerosis.…”
Section: Discussionmentioning
confidence: 96%
“…Cyclophosphamide, a clinically potent immunosuppressant, acts as an antiinflammatory agent by effectively blocking the release of cytokines. Immunoglobulin index refers to immune protein components extracted from healthy plasma and purified and formulated through a series of processes [16]. The use of prednisone in combination with immunesuppressive therapy for SLE patients boosts immunity thereby improving the patient's conditions.…”
Section: Discussionmentioning
confidence: 99%